2022
DOI: 10.15414/raae.2022.25.02.24-32
|View full text |Cite
|
Sign up to set email alerts
|

Profit Efficiency of Smallholder Maize Farmers in Sagnarigu Municipal of Northern Ghana

Abstract: Research background: Maize is the most important cereal crop produced by most households in Ghana for income and household food security. Despite its economic importance, not much study has been carried out on maize profit efficiency in Ghana, hence this study. Purpose of the article:This study estimated profit efficiency of maize farmers in the Sagnarigu municipal of Ghana to understand producers' profit efficiency level and its determinants as well as the challenges faced by maize producers. Methods: Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Maize farmers from Kenya's northern region were noted as having a mean PE equal to 0.68 by Ref. [ 70 ]. According to Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Maize farmers from Kenya's northern region were noted as having a mean PE equal to 0.68 by Ref. [ 70 ]. According to Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study demonstrated that most (52.69%) rice farming practices in the tidal swampland of South Sumatra are not efficient [84]. Meanwhile, a wide range of TE level diversity is also demonstrated by a study in Bangladesh, which shows TE values ranging from 0.16 to 0.94 [63] and in Ghana, ranging from 0.11 to 0.98 [32].…”
Section: Distribution Of Te Ratingmentioning
confidence: 90%
“…Generally, farmers use their own capital for farming costs because it is not easy to access bank loans. A previous empirical study conducted by Anang et al [63] found that access to credit positively affects TE. The easier it is for farmers to access credit sources, the higher the TE of agricultural businesses.…”
Section: Local Rice Farming In the Study Areamentioning
confidence: 91%